In Vivo Evaluation of Butterfly Pea (Clitoria ternatea) Flower Gel on IL-10 and STAT3 Expression in Thermally Induced Skin Burns - Mediana, Mecha Amalia; Hussaana, Atina; Trisnadi, Setyo (Journal of Health and Nutrition Research, 2025)
Burn injuries caused by thermal exposure trigger oxidative stress and inflammation, largely driven by reactive oxygen species (ROS) and systemic inflammatory response syndrome (SIRS). These mechanisms may disrupt the production of cytokines involved in tissue repair, such as interleukin-10 (IL-10) and signal transducer and activator of transcription 3 (STAT3). Clitoria ternatea L. (butterfly pea) contains potent antioxidant and anti-inflammatory phytochemicals, making it a promising candidate for modulating inflammatory responses and promoting wound healing. This study evaluated the effects of Clitoria ternatea extract gel on IL-10 and STAT3 expression in second-degree burn injuries using a Wistar rat (Rattus norvegicus) model. A post-test only control group design was employed, involving 30 male rats randomly assigned to five groups (G1–G5). Second-degree burns were induced using a 1.8 cm diameter heated metal plate applied to the dorsal skin for 3 seconds after heating for 15 minutes. Treatments with the extract gel were administered topically for seven days. Skin samples were collected 24 hours after the last application and analyzed for IL-10 and STAT3 mRNA expression using qRT-PCR. Data were statistically tested with One-Way ANOVA. The results showed no significant differences in IL-10 expression among all groups. However, STAT3 expression was significantly higher in the groups treated with 5% and 10% Clitoria ternatea extract gel, with the highest observed in the 10% group (6.73 ± 2.94). These findings indicate that while IL-10 remained unaffected, butterfly pea extract gel effectively increased STAT3 expression, suggesting its potential role in modulating regenerative pathways in burn-injured skin